2011
DOI: 10.1159/000329161
|View full text |Cite
|
Sign up to set email alerts
|

Response to Growth Hormone Treatment in Isolated Growth Hormone Deficiency versus Multiple Pituitary Hormone Deficiency

Abstract: Background: Growth hormone (GH) therapy successfully increases height prognosis in children with GH deficiency (GHD); however, adult height data are still limited. Aim: This study investigated near-adult height (NAH) in patients with idiopathic GHD (i.e. those with a GH peak <10 µg/l with no organic pathology) divided into two groups: isolated GHD and multiple pituitary hormone deficiency (MPHD). Methods: All patients were registered in the Pfizer International Growth Study Database (KIGS). Median (10th to 90t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
41
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 35 publications
(40 reference statements)
10
41
1
4
Order By: Relevance
“…We cannot explain the greater response in our MPHD group, which persisted after corrections for differences in height at start and distance to target height. Concordant with our study, Darendeliler et al [26] found a significantly (p < 0.001) higher growth response in prepubertal children with MPHD (n = 554) compared to isolated GHD (n = 1,619). The children with MPHD in that study were significantly younger and shorter at start of GH treatment compared to those with isolated GHD.…”
Section: Discussionsupporting
confidence: 92%
“…We cannot explain the greater response in our MPHD group, which persisted after corrections for differences in height at start and distance to target height. Concordant with our study, Darendeliler et al [26] found a significantly (p < 0.001) higher growth response in prepubertal children with MPHD (n = 554) compared to isolated GHD (n = 1,619). The children with MPHD in that study were significantly younger and shorter at start of GH treatment compared to those with isolated GHD.…”
Section: Discussionsupporting
confidence: 92%
“…In previous studies, the difference between final height and TH was -0.2 SDS in boys and -0.5 SDS in girls [13], while 89% of IGHD patients and 81% of MPHD patients achieved their genetic height potential [16]. Unphysiologic hormone supplementation or poor adherence to treatment may have contributed to lower rates of achievement of parental TH in MPHD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The mammary ductal defects in Gli2 ΔS mice thus are not rescued by growth hormone, but are rescued by local supplementation with the stromally-expressed paracrine factors induced by growth hormone (Igf1 and Wnt2b) (Zhao et al, 2017). This type of niche failure may explain the pathogenesis of certain human diseases sometimes associated with GLI2 mutation, including the deficient breast development and hormonal insensitivity associated with the human disorder combined pituitary hormone deficiency, (Darendeliler et al, 2011; Maghnie et al, 2006). How mammary niche function may contribute to breast cancer pathogenesis, however, remains unclear.…”
Section: Specification Of the Stromal Niche In Bladder And Mammary Glandmentioning
confidence: 99%